Understanding why collective action resulted in greater advances for tobacco control as compared to alcohol control during the Philippines’ Sin Tax Reform: a qualitative study - Hoe, Connie; Weiger, Caitlin; Cohen, Joanna E. (BMJ open, 2022)
Background and aims In 2012, the Philippines passed a law popularly known as the ‘Sin Tax Reform’. This law increased excise tax on both tobacco and alcohol. While a victory for public health, the total amount of taxes paid by the tobacco and alcohol industries was an uneven 69-31 split. The primary aim of this study is to explore why collective action of Sin Tax proponents resulted in greater advances for tobacco control as compared with alcohol control. - Methods A case study approach was used. Key informant interviews were carried out with 25 individuals from academic, governmental, non-governmental and international organisations and industry who had first-hand knowledge of the Sin Tax policy process, led an organisation that participated in the process and/or possessed expert knowledge of Sin Taxes in the Philippines. Interviews were subsequently transcribed then analysed using inductive coding. - Results Four factors contributed to the varying tax treatment of the two industries: (1) absence of advocacy-oriented alcohol control groups, (2) the proponents’ ‘divide and conquer’ strategy, which aimed to prevent the alcohol and tobacco industries from joining forces, (3) the perception that moderate drinking is acceptable among some of the Sin Tax proponents, public and medical community and (4) a weaker global push for alcohol control. - Conclusions Our findings suggest the need to cultivate advocacy-oriented alcohol control civil society organisations, generate consensus at the local and global level regarding the problem definition and policy solutions for alcohol control and consider global instruments to strengthen norms and standards for alcohol control. Given that proponents also negotiated for a lower alcohol tax compared with tobacco due to the concern that the two industries might join forces, it also raises the question of whether or not a health tax bill should tackle more than one health harming product at a time.
Gesehen am 01.07.2022